Professional Gender Segregation in Scientific Discourse: Trends and Contradiction - A. Yu. Kolianov (Дискурс)
Introduction. The article examines current ideas about professional gender segregation in Russian and foreign scientific discourses. Comparative analysis of various approaches to understanding gender issues allows us to identify new potentials for their study, as well as to pay attention to the development of the optics of Russian science in considering gender differences. Gender issues in the field of information technology require the closest attention and study, since this area is at the forefront of scientific, technological and social development.Methodology and sources. The theoretical and methodological basis for interpreting the results of the study was the main provisions of sociological and economic theories: the theory of social representations (S. Moscovici), the concept of habitus (P. Bourdieu), role theory (R. Linton), and rational choice theory. To work with empirical data, we used the methods of comparative text analysis, analysis of documents and research reports (The Gender Inequality Index, The Global Gender Gap Index, Global Gender Gap Report, “Women and Men of Russia-2022”), and discourse analysis.Results and discussion. In foreign studies, with the long-established vision and acceptance of gender problems, there is an understanding that past steps to achieve gender parity in the labor market lead to a new configuration of gender differences, which requires new efforts to eliminate them. In Russian scientific literature, the main emphasis is on monitoring the current situation of women in the professional environment, analyzing statistics and searching for hidden mechanisms of professional gender segregation.Conclusion. The results of the analysis show that in the presence of demonstrative statistics and large-scale empirical research, there is no theoretical consensus in the scientific discourse about the professional gender situation. There is a clear dissonance between the statement of problems by theorists and the lack of a request to find their solution on the part of practice, where gender “neutrality” or “indifference” reigns in some professional contexts. Conclusions are drawn about the nature of the Russian scientific gender discourse, which needs to develop a thesaurus of nonbinarity and develop an effective way of reasoning about gender issues.